AUSTRALIAN HUMAN RIGHTS COMMISSION (AHRC) DALAM MENGURANGI KASUS DISKRIMINASI RAS DI AUSTRALIA TAHUN 2015-2018 - Micaella Dani; Muharjono Muharjono (Jurnal Paradigma, 2020)
This journal discussing about the efforts of the Australian Human RightsCommission (AHRC) to reduce racial discrimination cases in Australia 2015-2018. The AHRC efforts was defined into five rules and procedures for resolving racial discrimination complaints. They are socialization or early warning, collecting complaints and investigation, fulfillment, continuation of legal actions, and public hearings. The Australia’s moment ratified the rules of the United Nations of Human Rights Commissioner (UNHRC), namely the CERD rules concerning the International Convention on the Elimination of All Forms of Racial Discrimination which sparked the 1975 Racial Discrimination Act could construct the formation of the AHRC in 1986. The principle of UNHRC is an organization known as regime which adopted in Australia in the form of AHRC. This journal aims to discuss, describe and find out the efforts of the Australian Human Rights Commission in reducing cases of racial discrimination in Australia 2015-2018. Explain the rules and procedures for resolving racial discrimination complaints received by the AHRC through five stages of resolution. Afterwards analyze whether the five rules and procedures implemented by the AHRC implemented optimally to reduce racial discrimination cases which happened in Australia in 2015-2018.